EFISIENSI TEKNIS USAHATANI JAGUNG (Zea mays) DI DESA BIATAN ILIR KECAMATAN BIATAN KABUPATEN BERAU (Technical Efficiency of Corn (Zea mays) Farming in Biatan Ilir Village Biatan Subdistrict Berau District) - HERWAN GALINGGING (Universitas Mulawarman (University of Mulawarman), 2020)
This research aimed to analyze the technical efficiency level of inputs utilization on corn farming. This research was conducted in Biatan Ilir Village, Biatan Subdistrict, Berau District, East Kalimantan Province. The sample number was 32 respondents determined by simple random sampling. Data is analyzed by using the frontier production function of Cobb-Douglas. The result of this research showed the average of corn yield in Bintan Ilir Village as many as 1,885.21 kg ha-1. The utilization of seed, fertilizer, insecticide, and labor simultaneous influence significantly on corn yield. However, only fertilizer and labor partially influence corn yield. It was only 9.37% respondents efficiently cultivated corn in term technical. Corn farming in Biatan Ilir Village is in the stage of increasing return to scale.